THE EFFECT OF CAPITAL ADEQUACY RATIO (CAR), NET INTEREST MARGIN (NIM), AND LOAN TO DEPOSITS RATIO (LDR) ON RETURN ON ASSET (ROA) IN PT BANK NEGARA INDONESIA PERSERO TBK PERIOD OF 2011-2021 - Permata Rahmi, Palupi; Herlina, Listri; Novitasary, Shanty (Universitas Indonesia Membangun (Inaba), 2022)
One measure to assess the level of soundness or performance of a bank's profitability is Return On Assets (ROA). The level of Return On Assets (ROA) is used to measure bank profitability and focuses on the company's ability to earn profits in its operations, Bank Indonesia sets a minimum amount of Return On Assets (ROA) of 1.5%. However, the Return on Assets (ROA) at PT Bank Negara Indonesia Persero, Tbk for the 2011-2021 period fluctuated with a downward trend. Many factors can affect the rise and fall of Return On Assets (ROA). This study aims to explain the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Loan to Deposits Ratio (LDR) on Return On Assets (ROA). This research uses quantitative methods with descriptive and verification approaches. The type of data is secondary data sourced from www.idx.co.id and the annual report of PT Bank Negara Indonesia, Tbk. The data analysis method used is descriptive analysis and verification analysis (classical assumption test, multiple regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing). The results showed that: 1) Return on Assets (ROA) fluctuated with a downward trend with an average of 2.53% and a standard deviation of 0.87. 2) Capital Adequacy Ratio (CAR) fluctuates with a downward trend with an average of 17.97% and a standard deviation of 1.59. 3) Net Interest Margin (NIM) fluctuated with a downward trend with an average of 5.63% and a standard deviation of 0.68%. 4) Loan to Deposits Ratio (LDR) fluctuates with an increasing trend with an average of 84.79% and a standard deviation of 6.36. 5) Capital Adequacy Ratio (CAR) has no significant effect on Return On Assets (ROA). 6) Net Interest Margin (NIM) has a significant effect on Return On Assets (ROA). 7) Loan to Deposits Ratio (LDR) has no significant effect on Return On Assets (ROA). 8) Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Loan to Deposits Ratio (LDR) simultaneously (together) have a significant effect on Return On Assets (ROA). With the influence contribution of 67.50%, while the remaining 32.50% is influenced by other factors that are not included in the study.